2017
DOI: 10.1038/srep45506
|View full text |Cite
|
Sign up to set email alerts
|

Urine metabolomics in neonates with late-onset sepsis in a case-control study

Abstract: Although late-onset sepsis (LOS) is a major cause of neonatal morbidity and mortality, biomarkers evaluated in LOS lack high diagnostic accuracy. In this prospective, case-control, pilot study, we aimed to determine the metabolic profile of neonates with LOS. Urine samples were collected at the day of initial LOS evaluation, the 3rd and 10th day, thereafter, from 16 septic neonates (9 confirmed and 7 possible LOS cases) and 16 non-septic ones (controls) at respective time points. Urine metabolic profiles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 51 publications
6
59
0
1
Order By: Relevance
“…Future studies should examine whether measurement of markers of catabolic stress soon after birth can help identify neonatal sepsis in infants who would otherwise not be considered at risk for the condition. Our findings complement those recently published by Sarafidis and colleagues 44 , whose study found substantial differences in the metabolic profiles of urine samples from septic and non-septic infants. As with our study, they also noted significantly heightened levels of several amino acids among late-onset neonatal sepsis cases, which the authors hypothesized may suggest disturbances in protein metabolism 44 .…”
Section: Discussionsupporting
confidence: 92%
“…Future studies should examine whether measurement of markers of catabolic stress soon after birth can help identify neonatal sepsis in infants who would otherwise not be considered at risk for the condition. Our findings complement those recently published by Sarafidis and colleagues 44 , whose study found substantial differences in the metabolic profiles of urine samples from septic and non-septic infants. As with our study, they also noted significantly heightened levels of several amino acids among late-onset neonatal sepsis cases, which the authors hypothesized may suggest disturbances in protein metabolism 44 .…”
Section: Discussionsupporting
confidence: 92%
“…82 Another recent study also used nuclear magnetic resonance and targeted liquid-chromatography MS to analyze samples from infants with both confirmed and suspected NS, and revealed other distinctive changes in urinary metabolites. 83 These changes relative to age-matched controls were most distinctive at the first suspicion of infection, with differences becoming insignificant by day 10 of the illness. This study also noted an increase in urinary lactate; however, significant differences were also noted in 16 other metabolites, including taurine and hypotaurine, which were postulated to be part of a protective anti-inflammatory response.…”
Section: Genomics Proteomics and Metabolomicsmentioning
confidence: 91%
“…Late-onset neonatal sepsis: sepsis diagnosed among neonates at the age of 7 days or more [24,26,28].…”
Section: Definitionsmentioning
confidence: 99%
“…Early diagnosis of sepsis improves survival and functional outcome [28,29]. The other benefit of an early and correct diagnosis is related to antibiotic consumption.…”
Section: Introductionmentioning
confidence: 99%